Arabic Isolated Digits Recognizer System - Ben-Mahfouz, Mohammed Omer; Asaad, Abdul Raqib Abdo (University of Science and Technology, Sana'a, 2003)
This paper presents a study performed on the ten Arabic digits (0, 1, 2, ..., 9) waveforms for male and female speakers. The features used were the LPC coefficients of a 12-pole analysis, and the simple Euclidean distance measure was used to measure the similarity between the patterns with the digit templates obtained, Recognition accuracies for new male speakers using Crisp k-Mean were about 75% and using Fuzzy c-Mean were about 82%. But for new female speakers no change from the 75% using the two methods was recorded. Using the same speakers, the accuracies were about 90% for male speakers and about 75% for female speakers.